Risk Factors of Pulmonary Tuberculosis in the Working Area of Perumnas Public Health Center Kendari City - Andi Mauliyana; Evi Hadrikaselma (MIRACLE Journal Of Public Health, 2021)
Kendari City is the area with the highest number of TB cases in Southeast Sulawesi Province with a total of 488 cases in 2019. Preliminary data at the Perumnas Public Health Center showed that there were 49 TB cases in 2019. This study aims to determine the risk factors for the incidence of pulmonary TB in the Work Area. Public Health Center. This study uses a case control design. The study population was 105 patients, with a sample consisting of 44 case samples and 44 control samples, which were taken by simple random sampling. Data analysis using Chi Square test and Odds Ratio. From the results of the study, it was found that there were significant risk factors between smoking habits (OR = 5,156), contact history (OR = 8,333), occupancy density (OR = 2,544), knowledge (OR = 3,852) and ventilation (OR = 3,071) with the incidence of pulmonary tuberkulosis. The conclusion of this study is smoking habits, contact history, occupancy density, knowledge, and ventilation are risk factors for the incidence of pulmonary tuberkulosis at the Perumnas Public Health Center. Therefore, it is suggested to the health workers of the Puskesmas are expected to continue to provide health promotion and improve work programs related to pulmonary TB in order to increase knowledge and awareness of the community to prevent transmission of pulmonary TB.